2017
DOI: 10.1111/1745-9125.12161
|View full text |Cite
|
Sign up to set email alerts
|

Does the Gender Gap in Delinquency Vary by Level of Patriarchy? A Cross‐national Comparative Analysis

Abstract: We examined cross‐national variation in the gender differential in offending, which is often referred to as the gender gap in crime. Analyses were directed toward two empirical questions: 1) Is the gender gap narrower in less patriarchal sociocultural settings, and if so, 2) is this outcome a result of higher levels of offending on the part of girls, lower levels of offending on the part of boys, or some combination thereof? To address these questions, we compiled a multilevel, cross‐national data set combinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…We focus on how parental social control is transformed into different levels of self-control among females and males and subsequently, into different rates of delinquency [51]. While studies analyzing the role of child-parent interactions on delinquency have typically used data from a national sample, few studies have examined differences in offending across countries [21,64]. The Savolainen et al study [64] used multi-level data from the International Self-Report Delinquency Survey (ISRD2) to examine the cross-national variation in gender gap in crime and found that the gender gap in delinquent offending is narrower when there are lower levels of patriarchy in a country.…”
Section: Parental Social Control and Self-reported Violent Delinquencymentioning
confidence: 99%
See 4 more Smart Citations
“…We focus on how parental social control is transformed into different levels of self-control among females and males and subsequently, into different rates of delinquency [51]. While studies analyzing the role of child-parent interactions on delinquency have typically used data from a national sample, few studies have examined differences in offending across countries [21,64]. The Savolainen et al study [64] used multi-level data from the International Self-Report Delinquency Survey (ISRD2) to examine the cross-national variation in gender gap in crime and found that the gender gap in delinquent offending is narrower when there are lower levels of patriarchy in a country.…”
Section: Parental Social Control and Self-reported Violent Delinquencymentioning
confidence: 99%
“…While studies analyzing the role of child-parent interactions on delinquency have typically used data from a national sample, few studies have examined differences in offending across countries [21,64]. The Savolainen et al study [64] used multi-level data from the International Self-Report Delinquency Survey (ISRD2) to examine the cross-national variation in gender gap in crime and found that the gender gap in delinquent offending is narrower when there are lower levels of patriarchy in a country. Generally, patriarchy can be understood as a system where relations between men and women are perceived as "hierarchical relations of superiority and inferiority" [65] (p. 3).…”
Section: Parental Social Control and Self-reported Violent Delinquencymentioning
confidence: 99%
See 3 more Smart Citations